Learn JavaFX 17 : building user experience and interfaces with Java - Sharan, Kishori (Software engineer); Späth, Peter (Apress, 2022)
This unique in-depth tutorial shows you how to start developing rich-client desktop applications using your Java skills and provides comprehensive coverage of JavaFX 17's features. Each chapter starts with an introduction to the topic at hand, followed by a step-by-step discussion of the topic with small snippets of code. The book contains numerous figures aiding readers in visualizing the GUI that is built at every step in the discussion. This book has been revised to include JavaFX 17 and earlier releases since previous edition. It starts with an introduction to JavaFX and its history. It lists the system requirements and the steps to start developing JavaFX applications. It shows you how to create a Hello World application in JavaFX, explaining every line of code in the process. Later in the book, authors Kishori Sharan and Peter Späth discuss advanced topics such as 2D and 3D graphics, charts, FXML, advanced controls, and printing. Some of the advanced controls such as TableView, and WebView are covered at length in separate chapters. This book provides complete and comprehensive coverage of JavaFX 17 features; uses an incremental approach to teach JavaFX, assuming no prior GUI knowledge; includes code snippets, complete programs, and pictures; covers MVC patterns using JavaFX; and covers advanced topics such as FXML, effects, transformations, charts, images, canvas, audio and video, DnD, and more. So, after reading and using this book, you'll come away with a comprehensive introduction to the JavaFX APIs. You will: Build JavaFX User Interfaces and Java clients Understand properties, bindings, observable collections, stages, scenes; how to use these Play with colors, styling nodes and event handling Add user interactivity (mouse, keyboard, DnD) Use tables, trees and tree tables Create 2D shapes, text nodes, and 3D shapes Apply effects, transformations, animations, images Learn to draw and play audio and video.